Spirocyclopropane-type sesquiterpene hydrocarbons from Schinus terebinthifolius Raddi. - Richter, Rita; von Reuss, Stephan H; König, Wilfried A (My University, 2010)
The essential oil of Schinus terebinthifolius fruits was reinvestigated using GC and GC-MS techniques. Apart from several known compounds three sesquiterpene hydrocarbons with a carbon skeleton exhibiting the rare spiro(cyclopropane) moiety could be isolated by a combination of column chromatography and GLC. Structure assignments were carried out by NMR spectroscopy. These natural products are 9-spiro(cyclopropa)-4,4,8-trimethyl-2-methylenbicyclo[4.3.0]non-1(6)-ene (terebanene), 9-spiro(cyclopropa)-2,4,4,8-tetramethylbicyclo[4.3.0]nona-1,5-diene (teredenene), and (6R*,8R*)-9-spiro(cyclopropa)-2,4,4,8-tetramethylbicyclo[4.3.0]non-1-ene (terebinthene).
Keywords: Schinus terebinthifolius; Anacardiaceae; Sesquiterpene hydrocarbons; Spirocyclopropane; Terebinthane; Terebanene; Teredenene; Terebinthene